Reaching Into the Dark Side of Organisations: The Banality and Emergence of Administrative Evil in the Light of Two Case Examples - Virtanen, Petri; Lehtonen, Tommi; Raisio, Harri (Scandinavian Journal of Public Administration, 2022)
This article uses the tools and distinctions derived from a twofold analysis to develop and refine the perception of administrative evil. First, the general problem of evil is discussed and nuanced, and second, two case examples from the Finnish context are examined and explained – the notion of so-called old boys’ networks and the case of unethical behaviour in a psychiatric hospital. The article defines administrative evil as actions by civil servants and government employees when they do what they are expected to do to fulfil their organisational roles and responsibilities without considering or recognising that they are engaging in or contributing to evil. Based on a conceptual analysis, the article suggests that administrative evil is a middle form between moral and natural evil. This view yields a solid basis for further analysis in which the concept of the banality of evil – as introduced by Hannah Arendt – provides valuable insights. The article is based upon the conviction that the concept of administrative evil offers explanatory power to understand and describe why and how people behave badly and even unethically in organisational contexts. In doing so, the article connects the concept of administrative evil to organisational studies and links the concept with the distinction between types of evil. The paper concludes that a major problem in theorising administrative evil is that the concept (as advanced by Adams and Balfour) has remained isolated and is not an organic part of modern organisation theory.